A Review of the Antibacterial Properties of Selected Southern African Plant Species Used in Traditional Medicine - Kim, Jinwoo; Cock, Ian Edwin; Cheesman, Matthew James (Pharmacognosy Communications)
Introduction: The rise in bacterial resistance has caused significant global health challenges and reduced the effectiveness of antibiotics. For thousands of years, plants have been used in traditional medicine to combat disease associated with infections, serving as natural remedies due to their antimicrobial properties. Aim of the Study: This study aimed to review and summarise the antibacterial properties of selected South African plant species and its ethnobotanical use, with the aim of promoting further studies in this area. Materials and Methods: Original scientific literature, reviews and online databases were searched to identify plant species traditionally used for treating bacterial infections in South Africa. A subsequent search was conducted to find studies that focuses on antibacterial activity of these plant species, summarising the existing knowledge and highlighting areas for further investigations. Results: 6 plant species traditionally used in South Africa to treat bacterial infections were investigated. Roots, barks, leaves, stems and fruits were the most utilized plant parts. These parts were often ground into a fine powder and extracted with water for consumption. Of these, only five plant species have been scientifically studied for antibacterial activities. Those studies screened against limited bacterial panels and generally did not focus on the mechanisms of action and safety for therapeutic applications. Conclusion: The selected plant species have significant antibacterial potential to, although the previous research has primarily focused on a narrow range of bacterial species. Further studies are required to investigate these plant-based medicines against a boarder spectrum of bacterial strains. Additionally, studies are required to isolate and identify the phytochemicals responsible for their activity and to elucidate their mechanisms. Comprehensive studies should be undertaken to evaluate the efficacy and safety of these plant-derived treatments for potential therapeutic applications.
Keywords: Antibacterial; Ethnobotany; Bacterial resistance; African plants; Traditional medicines.